A coalition of lineages : the Fernandeño Tataviam Band of Mission Indians - Champagne, Duane; Goldberg, Carole E. (The University of Arizona Press, 2021)
"The experience of the Fernandeño Tataviam Band of Mission Indians is an instructive model for scholars and provides a model for multicultural tribal development that may be of interest to recognized and nonrecognized Indian nations in the United States and elsewhere."--